Adopsi Teknologi Kecerdasan Buatan (AI) dalam Pelaporan Pajak: Studi Persepsi Kemudahan dan Keamanan Data Wajib Pajak Milenial - Lina Nurlaela; Marti Dewi Ungkari (Jurnal Algoritma, 2026)
Digital transformation in the public service sector has now expanded into tax administration through the integration of Artificial Intelligence (AI) systems. This study aims to analyze how millennial taxpayers perceive the use of AI technology in the tax reporting process, focusing on two main dimensions: system accessibility, or perceived ease of use, and personal data protection, or data security. Using a descriptive quantitative approach and SEM-PLS analysis involving 100 millennial taxpayer respondents, the findings reveal that AI technology is perceived as capable of simplifying the process of identifying and classifying tax objects. However, concerns regarding the confidentiality of personal information and the risk of data leakage remain real obstacles that limit the full adoption of the system.